Wykonaj ich redukcję:
a)1,2x-2y-5x+1,3y=
b)2/3a - 4/5b + 4/9 - 0,2b=
c)-3m - 7n + 4m - 15n +1=
d)0,05x - 0,07x*2 + 1,2x*2 - 0,07x - 1,05x*2=
e)-z - z*2 + 0,5z + 3,5 z +4,5z*2 =
f)-x +2y - z - 7 + 2x - 3y +z - 2=


Te razy 2 to potęgowanie 2

3

Odpowiedzi

2009-12-05T19:24:01+01:00
A)= -3,8x-0,7y
b)=2/3a-b+4/9
c)=m-22n+1
d)=0,08x²-0,02x
e)=3,5z²+3z
f)=x-y-9
2009-12-05T19:25:43+01:00
A) =-3,8x-0,7y
b) =2/3a-b+4/9
c) = m-22n+1
d) = 0,08x*2-0,12x
e) =3,5z*2+3z
f) = x-y-9
2009-12-05T19:27:51+01:00
A)=-3.8x-o.7y
b)2/3a-4.7b=4/9
c)m-22n=-1
d)0.05x-0.0049x+1.44x-0.07x-1.1025=1.49x-1.1774x=0.3126x
e)=3z+3.5z2
f)x-y=7+2
x-y=9